Penguatan Kapasitas Keislaman pada Peternak Lebah untuk Menghasilkan Madu Berkualitas Unggul - Rofiul Wahyudi; Nurul Suwartiningsih; Nursyiva Irsalinda; Jumadil Saputra (Universitas Sebelas Maret, 2023)
The Ayoh Ku Kelulut Beekeepers Community is a group of individuals actively involved in the endeavor of breeding Trigona sp. (stingless bee) honey bees in the area of Pengkalan Gelap, 2210 Kuala Setiu, Terengganu, Malaysia. The current challenge faced is the lack of understanding about the core values of beekeeping from an Islamic perspective. The purpose of this community engagement initiative is to provide comprehensive education, training, and guidance in the Islamic aspects related to beekeeping. All of these efforts are carried out with the intention of fostering enthusiasm among beekeepers, motivating them to tirelessly strive in producing exceptional quality honey. The implementation of this program is divided into two stages, involving sessions that deliver knowledge on the significance of bees and honey in the context of the Al-Qur'an and As-Sunnah, as well as training sessions focused on the wisdom associated with beekeeping and honey management. The positive impact of this step is the enhancement of beekeepers' understanding regarding the significance and relevance of beekeeping within the framework of Islamic teachings. This success is expected to strengthen the beekeepers' determination to care for the bees, thereby producing honey that meets higher quality standards.